2021
DOI: 10.29076/issn.2528-7737vol14iss35.2021pp43-53p
|View full text |Cite
|
Sign up to set email alerts
|

El Efecto de diversos atributos topográficos sobre el carbono orgánico en varios usos del suelo

Abstract: El objetivo de este estudio fue: cuantificar la cantidad de carbono orgánico del suelo (COS) almacenado en tres profundidades y relacionar varios atributos topográficos sobre la densidad del COS en el sitio El Progreso, provincia El Oro-Ecuador. El estudio se realizó en cuatro usos del suelo: banano, cacao joven, cacao maduro y cacao viejo, con valoresde COS entre cero a 0,10 m de 25,6 g kg, 35,8 g kg, 13,2 g kg y 10,5 g kg respetivamente, y las clases textural predominante son: franco arcillo limosa (0-0,10 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Thus, in this study, we found the behavior of several edaphic variables that are more affected by the local topography of the lot and by agronomic management (by allowing the growth of alder between the coffee trees) than by the conditions of biomass production and, therefore, of organic matter from this cover. In this regard, Barrezueta (2021) found important effects of surface runoff and topographic humidity index that end up strongly influencing the differences found in soil organic carbon accumulation in a study that also found differences due to coverage of bananas, young cocoa, ripe and old on a farm in the Oro province of Ecuador, located 500 meters above sea level.…”
Section: Resultsmentioning
confidence: 96%
“…Thus, in this study, we found the behavior of several edaphic variables that are more affected by the local topography of the lot and by agronomic management (by allowing the growth of alder between the coffee trees) than by the conditions of biomass production and, therefore, of organic matter from this cover. In this regard, Barrezueta (2021) found important effects of surface runoff and topographic humidity index that end up strongly influencing the differences found in soil organic carbon accumulation in a study that also found differences due to coverage of bananas, young cocoa, ripe and old on a farm in the Oro province of Ecuador, located 500 meters above sea level.…”
Section: Resultsmentioning
confidence: 96%